A Metal–Organic Framework Containing Unusual Eight‐Connected Zr–Oxo Secondary Building Units and Orthogonal Carboxylic Acids for Ultra‐sensitive Metal Detection. Issue 46 (7th October 2014) - Carboni, Michaël; Lin, Zekai; Abney, Carter W.; Zhang, Teng; Lin, Wenbin
Abstract Two metal–organic frameworks (MOFs) with Zr–oxo secondary building units (SBUs) were prepared by using p, p′‐terphenyldicarboxylate (TPDC) bridging ligands pre‐functionalized with orthogonal succinic acid (MOF‐1) and maleic acid groups (MOF‐2). Single‐crystal X‐ray structure analysis of MOF‐1 provides the first direct evidence for eight‐connected SBUs in UiO‐type MOFs. In contrast, MOF‐2 contains twelve‐connected SBUs as seen in the traditional UiO MOF topology. These structural assignments were confirmed by extended X‐ray absorption fine structure (EXAFS) analysis. The highly porous MOF‐1 is an excellent fluorescence sensor for metal ions with the detection limit of <0.5 ppb for Mn2+and three to four orders of magnitude greater sensitivity for metal ions than previously reported luminescent MOFs.